Pengelolaan Koleksi Audiovisual Di Era Digital: Studi Kasus Perpustakaan Nasional Republik Indonesia - Anggi Indah Puspita Sari; Fransiska Timoria Samosir; Sa'diyah, Lailatus (Institut Agama Islam Negeri (IAIN) Curup, 2025)
In the digital era which is increasingly developing rapidly, access to information and knowledge is no longer limited by time and space. Digital transformation, which involves converting physical data into digital format, has changed the way people access information, especially in managing audiovisual collections in national libraries. The aim of this research is to find out the steps in managing audiovisual collections in national libraries. This research is qualitative research with a descriptive approach. Research activities were carried out at the National Library of the Republic of Indonesia. Data collection techniques were carried out using observation, interviews and documentation. These results provide an understanding and explanation of the steps in managing audiovisual in the current digital era through the stages of checking library materials, inventory, classification, cataloging and other completeness such as adding labeling and tagging in managing audiovisual collections and with the advancement of technology this opens up opportunities for more efficient and easily accessible collection management, but on the other hand, this also raises various new challenges in terms of preservation, security, and copyright.